1983
DOI: 10.1149/1.2120034
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Characterization of α‐ and β‐Crystalline Silicon Nitride

Abstract: Silicon nitride, Si3N4 , used as a passivating layer in microelectronics, exists in the crystalline forms α‐Si3N4 and β‐Si3N4 and as amorphous material. Although the two crystalline modifications differ only slightly in their structure, it has been found that each modification can be distinguished by infrared spectroscopy. The spectral characteristics of α‐normaland β‐Si3N4 are described and a method for determining the concentration of one phase in the presence of the other has been developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
26
0
1

Year Published

1983
1983
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(32 citation statements)
references
References 0 publications
5
26
0
1
Order By: Relevance
“…1b) shows a broad band in the range of 800–1100 cm −1 which arises from the Si-N stretching vibration mode of α-Si 3 N 4 32. Moreover, several other absorption peaks around 370–700 cm −1 also correspond to the α-Si 3 N 4 crystalline structure33. Compared to those of the bulk α-Si 3 N 4 32, the absorption peaks at 1081 cm −1 , 1023 cm −1 , 977 cm −1 and 863 cm −1 here show a blue shift, which should be due to the size- and/or surface-induced quantum effects34.…”
Section: Resultsmentioning
confidence: 96%
“…1b) shows a broad band in the range of 800–1100 cm −1 which arises from the Si-N stretching vibration mode of α-Si 3 N 4 32. Moreover, several other absorption peaks around 370–700 cm −1 also correspond to the α-Si 3 N 4 crystalline structure33. Compared to those of the bulk α-Si 3 N 4 32, the absorption peaks at 1081 cm −1 , 1023 cm −1 , 977 cm −1 and 863 cm −1 here show a blue shift, which should be due to the size- and/or surface-induced quantum effects34.…”
Section: Resultsmentioning
confidence: 96%
“…Fig. 3 compares the FTIR spectrum from the sheet silicon sample with those from a-Si 3 N 4 prepared by different methods [9][10][11][12]. We can see that while the main features at B850 cm À1 are consistent, the structure of the a-Si 3 N 4 varies slightly with different preparation conditions.…”
Section: Methodsmentioning
confidence: 94%
“…The IR reflection spectra of SiC powder has a well defined mode centered at 800 cm À1 and a shoulder at about 900 cm À1 [21]. The first mode (around 500 cm À1 ) has been ascribed to the symmetrical Si±N±Si streching mode, the second mode (in the range 900±1000 cm À1 ) to the antisymmetrical Si±N±Si streching vibration [22,23]. The XRD spectrum of SiC powders clearly showed that there was no other structure presented except the cubic b-SiC phase (Figs.…”
Section: Discussionmentioning
confidence: 99%